The Bare Sensitivity That Lies at the Heart of Improvisation - Mayer-Foulkes, Benjamín (Critical Studies in Improvisation / Études critiques en improvisation, 2025)
Benjamín Mayer-Foulkes reflects on how Ajay Heble has impacted his life and work with 17, Instituto de Estudios Críticos, Mexico.